Ritual and politics : writing the history of a dynastic conflict in medieval Poland - Dalewski, Zbigniew, 1962- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2008)
Referring, by way of example, to the chronicler's story about a dynastic conflict in medieval Poland, this book offers an insight into the modes of using ritual as an effective tool of political action in the Middle Ages - both in the practice of political entreprising, and on the level of narrative information about that practice - and then reflects about the nature of the relationship between the reality of the written account and the reality of the practical activities described in it. It demonstrates the ways in which the reality of the narrative account and the reality of practics - ritual-in-text and ritual-in-performance - overlaid and interlaced one another, and exercised a mutual impact, thereby jointly creating a framework within which, in the earlier and high Middle Ages, political activity took place.